2017
DOI: 10.3311/ppci.10917
|View full text |Cite
|
Sign up to set email alerts
|

A Congestion Detection Based Traffic Control for Signalized Intersection

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In our case below 100°C ( T αβ ) and above 140°C ( T βα ) only the thermodynamically stable α‐iPP develops, because it has a higher growth rate than the β‐iPP. [ 48,49 ] If the conditions of crystallization favor the growth of the β‐form (ie, the temperature is between T αβ and T βα ), the formation of this less stable modification is also feasible as it is presented in Figure 1. Fan‐like formations of the β‐modification develop in the early stage of the crystallization.…”
Section: Crystallization Modelmentioning
confidence: 99%
“…In our case below 100°C ( T αβ ) and above 140°C ( T βα ) only the thermodynamically stable α‐iPP develops, because it has a higher growth rate than the β‐iPP. [ 48,49 ] If the conditions of crystallization favor the growth of the β‐form (ie, the temperature is between T αβ and T βα ), the formation of this less stable modification is also feasible as it is presented in Figure 1. Fan‐like formations of the β‐modification develop in the early stage of the crystallization.…”
Section: Crystallization Modelmentioning
confidence: 99%
“…Cavitation flow around isolated circular cylinders has been examined in experiments [15][16][17][18][19][20] . These studies analyzed the effect of bubble generation on the vortex structure and the behavior of pressure waves generated during bubble collapse.…”
Section: Introductionmentioning
confidence: 99%
“…The cavitation number is an index representing the ease of occurrence of cavitation, and the smaller the value, the more easily bubbles are generated. Varga and Sevestyen have investigated the relationship between the cavitation number, cavity length, and Strouhal number in the critical and supercritical Re range 15 . They reported that with decreasing cavitation number, the cavity length increases and the vortex shedding frequency decreases.…”
Section: Introductionmentioning
confidence: 99%
“…signal heads can be controlled without direct physical connection to the central controller unit. Moreover, the advent of Autonomous Vehicles (AV) make new technologies possible to be applied in traffic control [6][7][8]. AVs need to visually sense the signal heads to gather information of signal heads, or it can be provided via wireless communication.…”
Section: Introductionmentioning
confidence: 99%